2007
DOI: 10.1002/jssc.200600400
|View full text |Cite
|
Sign up to set email alerts
|

Analytical determination of antioxidants in tomato: Typical components of the Mediterranean diet

Abstract: Diets in the countries of the Mediterranean basin are characterised by abundant plant foods (fruits, vegetables, breads, nuts, seeds, wine, and olive oil) and include fish and low-fat dairy products. Among the vegetables, tomatoes are a main component of the traditional Mediterranean diet, which has been associated with health protection and longevity. Eating tomatoes has been associated with reduced risks of some types of cancer and other diseases. These beneficial properties appear to be related to the antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 69 publications
0
44
0
Order By: Relevance
“…Likewise, some authors have suggested that blood levels of lycopene and other carotenoids are simply indicative of a diet that includes fruits and vegetables. A growing body of evidence indicates that whole foods may be more effective than individual compounds for lowering disease risk (Clinton 2005, Gómez-Romero et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Likewise, some authors have suggested that blood levels of lycopene and other carotenoids are simply indicative of a diet that includes fruits and vegetables. A growing body of evidence indicates that whole foods may be more effective than individual compounds for lowering disease risk (Clinton 2005, Gómez-Romero et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Eating tomatoes has been associated with reduced risks of some types of cancer and other diseases [57]. Their constituents such as carotenoids and flavonoids contribute to the prevention of ultra violet ray damage in humans [58] and are efficient antioxidants capable of scavenging reactive oxygen species generated under conditions of photo-oxidative stress [59].…”
Section: Selected Components Of Mediterranean Diet Protecting Againstmentioning
confidence: 99%
“…Today, a number of analytical procedures have been developed and applied for the determination of antioxidants in fresh tomato and processed tomato products (Gomez-Romero et al, 2007) in a destructive and non-destructive way including electronic tongue (Rudnitskaya et al, 2001), colorimeter, electronic nose (Berna et al, 2002), the acoustic firmness sensor (AFS), near infrared spectroscopy (NIR) (Peirs et al, 2003;Yong et al, 2005;Baranska et al, 2006), nuclear magnetic resonance (NMR) (Gladdeny and Alexanderz, 1996), NIR-FT-Raman spectroscopy (Schulz et al, 2005), Fourier transform infrared spectroscopy (FTIR), hyperspectral imaging (Berna, 2006), etc.…”
Section: Original Researchmentioning
confidence: 99%